Education on the Internet (Journal of Parents and Teachers, 2014)
The following article offers multiple web pages that will make it easier for teachers to keep up to date educationally. Here we can find websites full of current news, resources, etc.
Keywords: teacher; students; pupils; resources; news; internet; websites; links; present